Hubungan Kualitas Pelayanan Kesehatan dengan Tingkat Kepuasan Pasien Jamkesmas Di Instalasi Hemodialisa Ruang Dahlia BLU RSUP Prof. DR. R. D. Kandou - Rahim, Regina F.; Lampus, Benedictus S.; Siagian, Iyone E.T. (UNIVERSITAS SAM RATULANGI, 2014)
Health is an important aspect in human’s life as well as a right for every human being. Many things need to be considered to increase the public’s health, one of them is to organize health service. Hospital is one of the health service. As a public service, a hospital is consist of many facilities and infrastructures such as medical instruments and health workers. He-modialysis is one of hospital’s service for chronic disease. Evaluation in hemodialysis unit in Virgin de los Lirios Hospital showed that there was 16,7% death of hemodialysis patient on 2005-2008. In United States, hemodialysis patient’s death was 23% each year and it was the highest in worldwide. In 2011, Indonesia had 15.353 patients, and in 2012 the number were increase to 19.621 patients. Chronic kidney disease prevalence in Indonesia on 2012 according to National Hospital Data & Information Center, the number of chronic kidney disease’s client is about 50 persons every one million popula-tion. The purpose of this study was to analyze relation between service quality (reliability, responsiveness, assurance, attention, tangibles) with satisfaction level of Jamkesmas patient in hemodialysis installation. This study was analytical study with cross sectional method. Sample in this study were 31 Jamkesmas hemodialysis patient as respondent. Fisher Exact test result shows that there is significant relation between health service quality in reliability category with Jamkesmas patient satisfaction level (p=0,04) and there is significant relation between health service quality in respon-siveness category with Jamkesmas patient satisfactionn level (p=0,001).Keywords: service quality, patient satisfaction, Jamkesmas, hemodialysis